Magnesium: Potential Roles in Neurovascular Disease - Chang, Jason J.; Mack, William J.; Saver, Jeffrey L.; Sanossian, Nerses (Frontiers in Neurology, 2014)
Objective: Magnesium therapy has been studied extensively in pre-clinical and clinical trials in multiple organ systems. Cerebrovascular diseases are particularly likely to benefit from its neuroprotective properties. This review summarizes current studies of magnesium in a wide range of neurovascular diseases. Methods: We searched relevant terms in the National Library of Medicine PubMed database and selected research including basic science, translational reports, meta-analyses, and clinical studies. Results: Studies examining magnesium administration in ischemic stroke have failed to show any benefit in clinical outcome. Data on magnesium for intracerebral hemorrhage is limited. Preliminary investigations in subarachnoid hemorrhage were promising, but definitive studies did not reveal differences in clinical outcome between magnesium and placebo-treated groups. Studies examining magnesium administration in global ischemia following cardiac arrest suggest a trend toward improved clinical outcome. The strongest evidence for clinically relevant neuroprotection following magnesium administration derives from studies of pre-term infants and patients undergoing cardiac bypass and carotid endarterectomy procedures. Magnesium was found to have an excellent safety profile across all investigations. Conclusions: Magnesium is easy to administer and possesses a favorable safety profile. Its utility as a neuroprotectant in cardiac surgery, carotid enderaterectomy, and pre-term infant hypoxia remain promising. Value as a therapeutic agent in ischemic stroke, intracerebral hemorrhage and subarachnoid hemorrhage is unclear and appears to be limited by late administration. Ongoing clinical trials assessing magnesium administration in the first hours following symptom onset may help clarify the role of magnesium therapy in these disease processes.